Global University Entrepreneurial Spirit Students' survey - National report 2016 Finland - Timo Pihkala; Elena Ruskovaara; Ulla Hytti (Lappeenranta University of Technology, 2022)
Student entrepreneurship is booming and along with the boom, also interest for student entrepreneurship has awakened. The Global University Entrepreneurship Student Spirit Survey GUESSS focuses on student entrepreneurship. This is now the fourth time when Finland is participating the GUESSS survey. The first one took place year 2006, and later on studies were carried out in 2008 and 2011. This GUESSS report highlights the state of the art of student entrepreneurship in Finland in 2016.